2009
DOI: 10.1097/med.0b013e32832d9f64
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine agonists and valvular heart disease

Abstract: Dopamine agonists are effective in treating prolactinomas. At typical doses, the risk for valvulopathy appears low. Increased risk of cardiac valvulopathy should be considered in patients requiring higher doses or long duration of therapy. Echocardiography should be performed in these high-risk patients, drug holidays implemented and patients withdrawn from these agents if possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Our database does not offer any information regarding the intake of dopamine agonists, which have been shown to induce valvular heart disease. 32 The diagnosis of diabetes itself or the higher rate of myocardial infarctions in the diabetes group might have led to an increased probability of seeing a cardiologist and receiving an echocardiogram and thus incidental detection of AS. Similarly, the fact that a guideline-compliant diagnosis of aortic valve stenosis was carried out is not documented for every single patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our database does not offer any information regarding the intake of dopamine agonists, which have been shown to induce valvular heart disease. 32 The diagnosis of diabetes itself or the higher rate of myocardial infarctions in the diabetes group might have led to an increased probability of seeing a cardiologist and receiving an echocardiogram and thus incidental detection of AS. Similarly, the fact that a guideline-compliant diagnosis of aortic valve stenosis was carried out is not documented for every single patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using high-dose D 2 -agonist therapy in Parkinson's disease patients have demonstrated cardiac valvular defects due to drug but in this Cushing's study, no patients developed deterioration of cardiac function, although one patient with a history of tricuspid regurgitation did develop worsening valvular function. 47 Of note, a majority of patients did experience improvement in hypertension and glucose intolerance, even in the absence of cortisol normalization. These findings renew interest in the potential use of dopamine agonists in Cushing's disease, although in many cases, high D 2 -agonist doses may be required.…”
Section: -Agonistsmentioning
confidence: 97%
“…It is recommended, if the dose of cabergoline is higher than 2 mg per week, that echocardiograms be performed periodically to monitor for heart valve abnormalities [8].…”
Section: Treatment Of Pituitary Adenomasmentioning
confidence: 99%